Wyzwania w nauczaniu na odległość i w wirtualnej klasie – zastosowanie programu Adobe Acrobat Connect Pro - MEDIC, Branko (Journal of Education, Technology and Computer Science, 2011)
This paper is my humble contribution to the advancement of Distance Tutoring and e-Learning in Serbia where technical requirements have made it possible for educators to develop their skills in tutoring online. The paper will examine some advantages and disadvantages of the leading industry platform Adobe Connect Pro Meeting and my personal experience in engaging students to develop their skills in presenting content online to other students of the world. The paper will also show that delivering classes online to the students of the world is a great challenge even for those lecturers who are fluent in English and are confident in their teaching approach and classroom management skills in the physical classroom. The experience of Distance Tutoring is certainly rewarding and the students have embraced the new technologies most enthusiastically because it gives them an opportunity to market their knowledge and skills even before they graduate from vocational schools or colleges.